Unveiling the Potential of Cmax f2 Factor Applied to Pilot Bioavailability/Bioequivalence Studies—A Case Study with Pazopanib Drug Products - Sara Carolina Henriques; Ana Leblanc; Sérgio Simões; Marlene Fonseca; Francisco Luís Pimentel; Luis Almeida; Nuno Elvas Silva (Pharmaceutics)
Background: When companies are uncertain about the potential of a new formulation to be bioequivalent to a Reference product, it is common practice to carry out downsized pilot studies as a gatekeeping in vivo strategy to decide whether to move forward or not with a full-size pivotal study. However, due to the small study size, these studies are inarguably more sensitive to variability. Objectives: To address and mitigate the uncertainty of the conclusions of pilot studies concerning the maximum observed concentration (Cmax), the f2 factor was proposed as an alternative approach to the average bioequivalence statistical methodology. Methods: In this work, the alternative methodology is applied to pharmacokinetic data from pilot bioequivalence trials performed with pazopanib 200 mg and 400 mg. Results: Despite the small sample size, and very high intra-subject variability, the f2 factor demonstrated the potential for predicting bioequivalence. The positive results were confirmed in the full sized pivotal studies. Conclusions: In conclusion, this alternate methodology shows promise in reducing uncertainty associated with pilot studies and aiding in decisions to go forward with pivotal bioequivalence studies.